An Improved Quasi-Z-Source DC-DC Converter with Continuous Input and Output Currents - Bussa V.K.; Yalla T.R.; Bussa V.; Yalla N.; Kobaku T.; Jeyasenthil R. (My University, 2025)
This article proposes an improved quasi-Z-source DC-DC converter (IqZSC) for a power conversion from low voltage sources (batteries, solar photovoltaic and fuel cells). It gives continuous input and output currents with less ripple due to presence of inductors at the input and output ports, unlike the basic quasi-Z-source converter (qZSC). Due to low ripple input current, it is a better choice for getting longer life span of the voltage sources. Also, it has common grounded output to eliminate measurement issues and electromagnetic interference (EMI) issues. As the IqZSC is developed from the qZSC by rearranging elements, it has equal number of elements as that of qZSC, and has two controlled switches which are operating at the same instant. Steady-state mathematical modelling of IqZSC is given and a comparative analysis is done by considering similar Z-source converters. Simulation studied are discussed to show the performance of the proposed converter. © 2023 IEEE.